2015
DOI: 10.1007/s10265-015-0738-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting invasions of Wedelia trilobata (L.) Hitchc. with Maxent and GARP models

Abstract: Wedelia trilobata (L.) Hitchc., an ornamental groundcover plant introduced to areas around the world from Central America, has become invasive in many regions. To increase understanding of its geographic distribution and potential extent of spread, two presence-only niche-based modeling approaches (Maxent and GARP) were employed to create models based on occurrence records from its: (1) native range only and (2) full range (native and invasive). Models were then projected globally to identify areas vulnerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…For example, Padalia et al (2014) examined the use of GARP and Maxent and reported that Maxent had a greater predicting power than GARP. However, Qin et al (2015) concluded the opposite; for large sample sizes (n > 150) like ours, which used 634 GARP training points, Terribile and Diniz-Filho (2010) reported that Maxent and GARP were similar in their predicted areas. One of the commonly stated weaknesses of GARP is its potential to overestimate the geographic range and generate false positives (Elith andGraham 2009, Sobek-Swant et al 2012).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, Padalia et al (2014) examined the use of GARP and Maxent and reported that Maxent had a greater predicting power than GARP. However, Qin et al (2015) concluded the opposite; for large sample sizes (n > 150) like ours, which used 634 GARP training points, Terribile and Diniz-Filho (2010) reported that Maxent and GARP were similar in their predicted areas. One of the commonly stated weaknesses of GARP is its potential to overestimate the geographic range and generate false positives (Elith andGraham 2009, Sobek-Swant et al 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Studies of roost selection by tree bats found that a closed canopy is an important variable for eastern red bats (Menzel et al 1998, Kalcounis-Rüppell et al 2005), so we included percent tree cover as a variable. Throughout different studies, elevation is used as a variable in some GARP models (Peterson et al 2002, McNyset 2005, Qin et al 2015 but not by others (Kostelnick et al 2007, Sobek-Swant et al 2012, Padalia et al 2014. These studies span a wide range of species and spatial scales that can affect whether to include elevation as a variable.…”
Section: Modeling Summer Rangesmentioning
confidence: 99%
“…Maxent is a general-purpose machine learning method with a simple and precise mathematical formulation, and it has a number of aspects that make it well-suited for modeling species distribution [31]. We selected this software for the following reasons: (1) MaxEnt Models are widely used in species distribution predictions [47]; (2) it is better at predicting the effect of climate change on species distribution and suitable area division compared to other ENMs, such as GARP and BLOCLIM [48]; (3) Maxent model results are more conservative [49]; and (4) Maxent estimates the distribution (geographic range) of a species by finding the distribution that has maximum entropy (i.e., is closest to geographically uniform), and this can be constrained based on the environmental conditions at recorded occurrence locations [50,51].…”
Section: Environmental Niche Modelsmentioning
confidence: 99%
“…From the conservation point of view, predicting geographical distribution of such hybrids is a first step in controlling their further spreading. Various modeling methods (heavily based on climatic data) have been used to predict distribution areas of naturalized or invasive plant species (e.g., Pattison and Mack, 2008;Qin et al, 2015;Wang and Xu, 2016). Unfortunately, there is a lack of study on modeling potential geographical distribution for hybrids between alien and native plant species that have the ability to produce their own offspring and become established.…”
Section: Introductionmentioning
confidence: 99%